Hungarosoma bokori Verhoeff, 1928 (Diplopoda: Chordeumatida): new insights into its taxonomy, systematics, molecular genetics, biogeography and ecology - Mock, Andrej; Tajovský, Karel; Žurovcová, Martina; Jarošová, Andrea; Kocourek, Pavel; Gruber, Jürgen; Angyal, Dorottya; Spelda, Jörg (Zootaxa, 2016)
Hungarosoma bokori Verhoeff, 1928 is a millipede species which was originally classified solely on the basis of a female specimen. Subsequently, a long history of field searching for and surmising about the systematic position of this small, enigmatic species followed. In April 2013, 85 years after its first description, a series of nine specimens were sampled in the type locality, the Abaliget Cave, in southern Hungary. An adult male was collected for the first time, along with females and juveniles. Descriptions of the gonopods and the female vulvae, both important for considerations of the systematic position of the species, are presented for the first time. Revision and re-designation of the type material was made. The cryptic life of the species is connected with its activity in winter, and its known fragmented distribution corresponds with its presence in undisturbed microhabitats having a specific microclimate, often in the soil at cave entrances. Molecular methods showed a positive detection of the intracellular prokaryotic parasite Wolbachia in H. bokori, reflecting its highly probable parthenogenetic character in the main part of its known area of occurrence. This is the first demonstration of Wolbachia in a millipede. The legitimacy of the family Hungarosomatidae Ceuca, 1974, as a separate taxon was analysed using morphological and molecular approaches. Results of both methods confirmed the existence of a distinct phyletic line. DNA barcoding has shown its closest position to Attemsiidae Verhoeff, 1899, or Neoatractosomatidae Verhoeff, 1901. Based on records from Austria, the Czech Republic, Hungary and Slovakia, the residual circum-pannonic distribution that the whole genus (family) probably represents is proposed.